Data initiatives for ocean-driven melt of Antarctic ice shelves - Sue Cook; Keith W. Nicholls; Irena Vaňková; Sarah S. Thompson; Benjamin K. Galton-Fenzi (Annals of Glaciology, 2022)
Ocean-driven melt of Antarctic ice shelves is an important control on mass loss from the ice sheet, but is complex to study due to significant variability in melt rates both spatially and temporally. Here we assess the strengths and weakness of satellite and field-based observations as tools for testing models of ice-shelf melt. We discuss how the complementary use of field, satellite and model data can be a powerful but underutilised tool for studying melt processes. Finally, we identify some community initiatives working to collate and publish coordinated melt rate datasets, which can be used in future for validating satellite-derived maps of melt and evaluating processes in numerical simulations.